Romance Philology, Berkeley, University of California Press, vol. XLVI, 1992. - Montes Giraldo, José Joaquín (Thesavrvs, 2022)
Brent A. Pitts, "In Praise of Tristan: Oral Composition and Epic Technique in Bcroul's Román de Tristan'. Roger Parks, '"El leñadory los enanitos': A Cripto-Jewish Versión of a Spanish Folktale". Noel Corbett, "What's New in Philology?". Helen Solterer, "Dismembering, Remembering the Chátelain de Couci". Ralph Penny, "Dialect Contact and Social Networks in JudeoSpanish". Diane M. Young, "Compensatory Processes and the Bimoraic Canon". Dana A. Nelson, "Oraciones condicionales en Gonzalo de Berceo y el Alexandre". John K. Walsh, "The Poem within the Trance (On St. John of the Cross)". Armin Schwegler, "El origen del español monicaco 'hombre de poco valor': un ejemplo de convergencia hispana, criolla y africana (con comentarios etimológicos sobre monigote y monifato)"